Unexpected Dynamic Binding May Rescue the Binding Affinity of Rivaroxaban in a Mutant of Coagulation Factor X - Zhang, Zhi-Li; Chen, Changming; Qu, Si-Ying; Ding, Qiulan; Xu, Qin (Frontiers in Molecular Biosciences, 2022)
A novel coagulation factor X (FX) Tyr319Cys mutation (Y99C as chymotrypsin numbering) was identified in a patient with severe bleeding. Not like earlier reported Y99A mutant, this mutant can bind and cleave specific chromogenetic substrate at normal level, suggesting an intact binding pocket. Here using molecular dynamics simulations and bing free energy calculations on a FX-rivaroxaban (RIV) complex, we confirmed the much stronger binding of RIV in Y99C than in Y99A on molecular level, which is actually the average result of multiple binding poses in dynamics. Detailed structural analyses also indicated the moderate flexibility of the 99-loop and the importance of the flexible side chain of Trp215 in the different binding poses. This work provides a case again that binding of ligand may not only a dynamic process, but also a dynamic state, which is often neglected in drug design and screening based on static crystal structures. In addition, the computational results somewhat support our hypothesis on the activated Tyr319Cys FX (Y99C FXa) with impaired procoagulant function to bind inhibitors of FXa and to be developed into a potential reversal agent for novel oral anticoagulants (NOAC).